The relationship between mental imagery and self-confidence in pupils engaged in school sports in the wilaya of tebessa cubs class - yahia khoudaifa; Hashishi Abdel Wahab (sports creativity, 2025)
The study aimed to reveal the relationship between mental Imagery and sport confidence in pupils engaged in school sports in the wilaya of tebessa cubs class, by identifying the level of mental imagery in the research sample, and the relationship between visual imagery, auditory imagery, motor sensation, emotional status and sport confidence. The study was based on a sample of (170) pupils, of whom (113) were involved in both group sports and (57) were involved in track and field athletics. The study used the Sport Imagery Questionnaire designed by Martinez 1982, which translated by ( راتب،1188 ), Trait Sport Confidence Inventory designed by (Vealey, 1986) which translated by ( عالوي،1889 ). The results indicated that the level of mental imagery was average. In addition, there is a statistical correlation at the level of 0.05 between visual perception, auditory imagery, motor sensation, emotional status and sport confidence.